Long-term reanalysis, future scenarios and impacts of nitrogen deposition on northern European ecosystems including the Baltic Sea and the Scandinavian Mountains - Camilla Andersson; Tinja Olenius; Helene Alpfjord Wylde; Elin Almroth-Rosell; Robert G. Björk; Mats P. Björkman; Filip Moldan; Magnuz Engardt (Science of The Total Environment, 2025)

The Impact of Variable DOC Concentrations on Acidification Assessments - Johanna Stadmark; Filip Moldan; Sara Jutterström; Bernard J. Cosby (Ecosystems, 2025)

Trends in mercury, lead and cadmium concentrations in 27 European streams and rivers: 2000–2020 - Karin Eklöf; Claudia von Brömssen; Brian Huser; Staffan Åkerblom; Algirdas Augustaitis; Hans Fredrik Veiteberg Braaten; Heleen A. de Wit; Thomas Dirnböck; David Elustondo; Ulf Grandin; Adéla Holubová; Sirpa Kleemola; et al. (Environmental Pollution, 2024)

Three Decades of Changing Nutrient Stoichiometry from Source to Sea on the Swedish West Coast - Mike Peacock; Martyn N. Futter; Sara Jutterström; Dolly N. Kothawala; Filip Moldan; Johanna Stadmark; Chris D. Evans (Ecosystems, 2022)
European ecosystems have been subject to extensive shifts in anthropogenic disturbance, primarily through atmospheric deposition, climate change, and land management. These changes have altered the macronutrient composition of aquatic systems, with widespread increases in organic carbon (C), and declines in nitrogen (N) and phosphorus (P). Less well known is how these disturbances have affected nutrient stoichiometry, which may be a more useful metric to evaluate the health of aquatic ecosystems than individual nutrient concentrations. The Swedish west coast has historically experienced moderate to high levels of atmospheric deposition of sulfate and N, and eutrophication. In addition, coastal waters have been darkening with damaging effects on marine flora and fauna. Here, we present three decades of macronutrient data from twenty lakes and watercourses along the Swedish west coast, extending from headwaters to river mouths, across a range of land covers, and with catchments ranging 0.037–40,000 km 2 . We find a high degree of consistency between these diverse sites, with widespread increasing trends in organic C, and declines in inorganic N and total P. These trends in individual macronutrients translate into large stoichiometric changes, with a doubling in C:P, and increases in C:N and N:P by 50% and 30%, showing that freshwaters are moving further away from the Redfield Ratio, and becoming even more C rich, and depleted in N and P. Although recovery from atmospheric deposition is linked to some of these changes, land cover also appears to have an effect; lakes buffer against C increases, and decreases in inorganic N have been greatest under arable land cover. Our analysis also detects coherently declining P concentrations in small forest lakes; so called (and unexplained) “oligotrophication.” Taken together, our findings show that freshwater macronutrient concentrations and stoichiometry have undergone substantial shifts during the last three decades, and these shifts can potentially explain some of the detrimental changes that adjacent coastal ecosystems are undergoing. Our findings are relevant for all European and North American waters that have experienced historically high levels of atmospheric deposition, and provide a starting point for understanding and mitigating against the trajectories of long-term change in aquatic systems.

Effects of ground surface permeability on the growth of urban linden trees - Emilia Sand; Janina Konarska; Alessandro W Howe; Yvonne Andersson-Sköld; Filip Moldan; Håkan Pleijel; Johan Uddling (Urban Ecosystems, 2018)

Ecosystem Services from Small Forest Patches in Agricultural Landscapes - Guillaume Decocq; Emilie Andrieu; Jörg Brunet; Olivier Chabrerie; Pieter De Frenne; Pallieter De Smedt; Marc Deconchat; Martin Diekmann; Steffen Ehrmann; Brice Giffard; Elena Gorriz Mifsud; Karin Hansen; et al. (Current Forestry Reports, 2016)

Assessing anthropogenic impact on boreal lakes with historical fish species distribution data and hydrogeochemical modeling - Salar Valinia; Göran Englund; Filip Moldan; Martyn N Futter; Stephan J Köhler; Kevin Bishop; Jens Fölster (Global Change Biology, 2014)
Quantifying the effects of human activity on the natural environment is dependent on credible estimates of reference conditions to define the state of the environment before the onset of adverse human impacts. In Europe, emission controls that aimed at restoring ecological status were based on hindcasts from process‐based models or paleolimnological reconstructions. For instance, 1860 is used in Europe as the target for restoration from acidification concerning biological and chemical parameters. A more practical problem is that the historical states of ecosystems and their function cannot be observed directly. Therefore, we (i) compare estimates of acidification based on long‐term observations of roach ( Rutilus rutilus ) populations with hindcast pH from the hydrogeochemical model MAGIC; (ii) discuss policy implications and possible scope for use of long‐term archival data for assessing human impacts on the natural environment and (iii) present a novel conceptual model for interpreting the importance of physico‐chemical and ecological deviations from reference conditions. Of the 85 lakes studied, 78 were coherently classified by both methods. In 1980, 28 lakes were classified as acidified with the MAGIC model, however, roach was present in 14 of these. In 2010, MAGIC predicted chemical recovery in 50% of the lakes, however roach only recolonized in five lakes after 1990, showing a lag between chemical and biological recovery. Our study is the first study of its kind to use long‐term archival biological data in concert with hydrogeochemical modeling for regional assessments of anthropogenic acidification. Based on our results, we show how the conceptual model can be used to understand and prioritize management of physico‐chemical and ecological effects of anthropogenic stressors on surface water quality.

Changes in Soil Dissolved Organic Carbon Affect Reconstructed History and Projected Future Trends in Surface Water Acidification - Jakub Hruška; Pavel Krám; Filip Moldan; Filip Oulehle; Christopher D. Evans; Richard F. Wright; Jiří Kopáček; Bernard J. Cosby (Water, Air, & Soil Pollution, 2014)

Modeling Past and Future Acidification of Swedish Lakes - Filip Moldan; Bernard J. Cosby; Richard F. Wright (Ambio, 2013)

Radial growth of Norway spruce and Scots pine: effects of nitrogen deposition experiments - Kristina Seftigen; Filip Moldan; Hans W. Linderholm (European Journal of Forest Research, 2013)

Riparian Zone Influence on Stream Water Dissolved Organic Carbon Concentrations at the Swedish Integrated Monitoring Sites - Mattias Winterdahl; Johan Temnerud; Martyn N. Futter; Stefan Löfgren; Filip Moldan; Kevin Bishop (Ambio, 2011)

Results from the Covered Catchment Experiment at Gårdsjön, Sweden, after Ten Years of Clean Precipitation Treatment - Filip Moldan; Richard A. Skeffington; Carl-Magnus Mörth; Peter Torssander; Hans Hultberg; John Munthe (Water, Air, & Soil Pollution, 2004)